Which McMaster egg counting technique is the most reliable? - Vadlejch, Jaroslav; Petrtýl, Miloslav; Zaichenko, Igor; Cadková, Zuzana; Jankovská, Ivana; Langrová, Iva; Moravec, Milan (Parasitology research, 2011)
This study focuses on the comparison of three selected modifications of the McMaster counting technique, namely the McMaster method modified by Wetzel (W) and Zajíček (Z), as well as the concentration McMaster technique according to Roepstorff and Nansen (R&N). These modifications differ in the weights of faeces examined (W, 2 g/Z, 1 g/R&N, 4 g), flotation solutions (W, NaCl/Z, MgSO(4) + Na(2)S(2)O(3)/R&N, NaCl + glucose), centrifugation (W, none/Z, 2,000 RPM for 2 min and 2,000 RPM for 1 min/R&N, 1,200 RPM for 5 min), number of McMaster chambers investigated (W, 3/Z, 2/R&N, 2), and multiplication factors used (W, 67/Z, 33/R&N, 20). To investigate the sensitivity and reliability of these methods, nematode eggs (Teladorsagia circumcincta) were used. Parasite elements are distributed through negative binomial distribution in naturally infected host faeces, and the number of parasite elements in a given amount of faeces sample is unknown to man. Therefore, we decided to prepare the exact number of eggs which were added to the parasite negative faeces; the faecal sample was then investigated. From this perspective, this is the first time a comparison of the McMaster methods has been so accurately investigated. This approach allows us to evaluate the real sensitivity and reliability of the tested method. As the findings of this study indicate, the highest sensitivity and reliability were obtained using the Roepstorff and Nansen modification. This McMaster modification is able to detect 20 eggs per sample (in 70% of samples). Concentrations of 200 and 500 eggs can be found in almost 100% of samples. Moreover, this method is simple, cheap and fast. For these reasons, we can recommend this method for routine veterinary practice.
Keywords: Feces; senzitivita a specificita; Trichostrongyloidea; Sensitivity and Specificity; Sheep; zvířata; feces; ovce; počet parazitárních vajíček; Parasite Egg Count; Animals